Long non-coding RNA and extracellular matrix: the hidden players in cancer-stroma cross-talk - Edoardo D'Angelo; Marco Agostini (Non-coding RNA Research, 2018)
Currently available high-throughput technologies combined with bioinformatics analyses revealed that nearly 80% of the genome is transcribed, whereas only 2% of the genetic code is translated in proteins. In the landscape of non-coding RNA, the long non-coding RNA (>200 nucleotides) is a newer class of ncRNAs, with a potential pivotal role in homeostatic and pathological mechanisms, confirmed by increasing emerging evidences in different diseases, especially in cancer. In parallel, recent studies have demonstrated that as cancer progresses, extracellular matrix co-evolves into an activated state through continuous biochemical and structural modifications. In this review, we synthesize these themes by exploring the functional cross-talk between lncRNAs and their involvement in ECM regulation and remodeling within the tumor microenvironment. Keywords: Long non-coding RNA, Extracellular matrix, Tumor microenvironment